Presidents, producers and politics: law-and-order policy in Brazil from Cardoso to Dilma. (4th May 2017) - Macaulay, Fiona
ABSTRACT: This article analyses the governance tools available to three Brazilian presidents – Fernando Henrique Cardoso, Luiz Inácio Lula da Silva and Dilma Rousseff – to direct and enact policy in the area of law-and-order, that is, to prevent crime, improve policing and develop effective penal responses. It examines the commonalities and the differences in the ways that each approached their key roles as president: communicating with the public on the issues, using the agencies of the federal bureaucracy, managing intergovernmental relations with the subnational units (states and municipalities), and managing their multiparty coalition and relations with Congress. In particular, it highlights the way in which Brazil's highly fragmented and porous party system, which underpins the country's coalitional presidentialist form of governance, has also encouraged the entry into legislative arenas of direct representatives of criminal justice professionals (police) and indirect representatives of private security actors. This has resulted in increasing producer capture of law-and-order policy within both the federal bureaucracy and legislative arenas at all levels of government. In the crisis of the Dilma presidency, to which they contributed, they were able to move from being veto-players to agenda-setters on law-and-order policy, intent on reversing the direction set by these presidents.